Application of evidence-based recommendations for heat acclimation: Individual and team sport perspectives. Issue 1 (2nd January 2019) - Pryor, J. Luke; Johnson, Evan C.; Roberts, William O.; Pryor, Riana R.
ABSTRACT: Heat acclimation or acclimatization (HA) occurs with repeated exposure to heat inducing adaptations that enhance thermoregulatory mechanisms and heat tolerance leading to improved exercise performance in warm-to-hot conditions. HA is an essential heat safety and performance enhancement strategy in preparation for competitions in warm-to-hot conditions for both individual and team sports. Yet, some data indicate HA is an underutilized pre-competition intervention in athletes despite the well-known benefits; possibly due to a lack of practical information provided to athletes and coaches. Therefore, the aim of this review is to provide actionable evidence-based implementation strategies and protocols to induce and sustain HA. We propose the following suggestions to circumvent potential implementation barriers: 1) incorporate multiple induction methods during the initial acclimation period, 2) complete HA 1–3 weeks before competition in the heat to avoid training and logistical conflicts during the taper period, and 3) minimize adaptation decay through intermittent exercise-heat exposure or re-acclimating immediately prior to competition with 2–4 consecutive days of exercise-heat training. Use of these strategies may be desirable or necessary to optimize HA induction and retention around existing training or logistical requirements.